The Kaliningrad region as a strategic exclave of the Russian Federation and its implications on the security issues of the Baltic states and Poland - Alaverdian, Karina (2023)
This thesis examines the Kaliningrad region as a strategic exclave of the Russian Federation and its implications on the security issues faced by the Baltic states and Poland in the light of securitization theory. The study critically analyzes the discursive practices employed by various actors to construct the region as a security concern. It also adds a comparison with an additional, third-party actor, and their interpretation of the region.